Media Buku Saku Bermuatan Keunggulan Seni Tari Lokal Kabupaten Pacitan untuk Meningkatkan Apresiasi Budaya pada Siswa SD - Saputra, Muhammad Aji; Ardhyantama, Vit; Tisngati, Urip (PGSD STKIP PGRI Pacitan, 2023)
This research aims to describe: (1) procedures for developing pocket book media; (2) feasibility of developing pocket book media; (3) the results of developing pocket book media to increase students' cultural appreciation. This type of research is research and development (R&D) with a 4D development model. Data collection techniques use observation, interviews, questionnaires and documentation. Data analysis uses product validity level techniques and trial data analysis. The research results show that: (1) pocket book media to increase students' cultural appreciation has been developed using a 4D development model with expert testing and validation; (2) Pocket book media is appropriate based on the assessment of material experts with an average score of 4